P0357VALIDATION OF THE ANCA RENAL RISK SCORE IN A LONDON COHORT: POTENTIAL IMPACT OF TREATMENT ON PREDICTION OUTCOME. (6th June 2020) - TAN, PEK GHE; O'Brien, Jennifer; Griffith, Megan; Condon, Marie; Cairns, Tom; Levy, Jeremy; Cook, Terry; Pusey, Charles; McAdoo, Stephen
Abstract: Background and Aims: A renal risk score was recently developed to predict the risk of progression to end stage kidney disease (ESKD) in patients with ANCA-associated glomerulonephritis (ANCA-GN). The score defines three risk groups, each with distinct renal survival at 36 months: 68% of high-risk patients reaching ESKD, compared to 26% and 0% in the medium- and low-risk groups, respectively. The majority of patients (101/115) used to define the risk score were treated with IV cyclophosphamide and steroids. At our centre, we employ a combined low-dose IV cyclophosphamide, rituximab and oral corticosteroid induction regimen, with or without plasma exchange (PEX) depending on disease severity, for ANCA-GN. A recent cohort study suggested this combination regimen may lead to better renal survival. We thus hypothesized that choice of remission-induction treatment may affect prediction accuracy of the risk tool. We retrospectively test the validity of the ANCA renal risk score in patients with ANCA-GN treated at our centre. Method: All patients with newly diagnosed, biopsy-proven ANCA-GN from 2006-19 were identified from local renal histopathology database. Patients with relapsing ANCA-GN, EGPA, other coexisting GN, or missing data on induction therapy or eventual renal outcome were excluded. ANCA-negative pauci-immune GN was included. Baseline demographics, ANCA serology, initial therapy and parameters in the ANCA risk score (including % normal glomeruli, % tubular atrophy and interstitial fibrosis (TAIF), and estimated glomerular filtration rate were collected. All patients were stratified using the risk tool and Kaplan Meier survival analysis was applied to examine the ESKD prediction. Subgroup analysis was then performed for patients who received the combination regimen of cyclophosphamide and rituximab. Results: 178 patients with a median follow up of 44 month were included in the analysis. The median age was 62 years and 82 patients (46%) were female. 94(53%) were MPO-ANCA positive, 66(37%) PR3-ANCA positive, 15 (8%) ANCA-negative, and 3 (2%) were double PR3/MPO-ANCA positive. 148 (83%) patients received the combination regimen, and 45 had concurrent PEX. Total of 37 (21%) patients reached ESKD. 29 (78%) of these, developed ESKD within 36 months of initial diagnosis. Using the risk score, 64(36%), 76(43%) and 38(21%) patients were deemed low-, medium- and high-risk, respectively. Very distinct poor renal survival at 36 months was seen in high-risk group (55% reaching ESKD, p<0.01), but was less apparent between low- (95%) and medium-risk (90%)(p=0.052) (Figure1); In the subgroup of patients treated with combination regimen without concurrent PEX, the high-risk subgroup continues to demonstrate poor renal survival at 36 months (60% ESKD), but renal survival between low- and medium-risk group were comparable (0 and 2% respectively, p=0.57) (Figure 2). Conclusion: In our cohort, the ANCA Renal Risk Score reliably predicted rapid ESKD progression at 36-month in high-risk patients, but was less accurate for distinguishing patients with low-and medium-risk. The subgroup analysis suggested combined cyclophosphamide and rituximab therapy may have modified long-term renal outcome especially in the medium-risk cohort, influencing the accuracy of the prediction tool. Large multi-centre cohorts are required to further evaluate the potential impact of treatment on predicting outcome.